Penerapan Media Permainan Congklak Dalam Meningkatkan Hasil Belajar Siswa Pada Konsep Perkalian - Safitri, Tia; Tiurlina, Tiurlina; Alfarisa, Fitri (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Education is a conscious effort to prepare students through guidance, teaching and/or training activities for their roles in the future. Mathematics is the science that studies quantity, structure, spatial shapes, and changes in numbers. Mathematics has concepts that are easier to understand if they are concrete, then they can be directed to the semi-concrete stage and finally mathematics can be understood abstractly by students. In this research, researchers used a qualitative approach as a research procedure that produces descriptive data, and quantitative research to collect, analyze and display data in numerical rather than narrative form. The method used was Classroom Action Research (CAR) on class II students at the State Elementary School of Kareo. In this research, it was found that a problem occurred, namely when teaching, the researcher found a problem, namely that there were deficiencies in students' mathematics learning outcomes in class II which showed that there were many students whose scores did not reach the standard (65). This happened because at that time the researcher as a teacher taught without the media and props used in learning and the lecture method was still used at the stage of understanding the concept of multiplication. Therefore, the way to overcome this is by using traditional game media such as Congklak. The instruments in the research are guide sheets for student tests, sheets for student observations, sheets for teacher observations. The research results show an increase in student learning outcomes. This increase was shown in the pre-cycle students who completed 31%, cycle I as much as 52% and cycle II as much as 83%.